2021
DOI: 10.1021/acs.chemmater.1c00204
|View full text |Cite
|
Sign up to set email alerts
|

N-type Semiconducting Polymers Based on Dicyano Naphthobisthiadiazole: High Electron Mobility with Unfavorable Backbone Twist

Abstract: Development of n-type semiconducting polymers is essential for organic electronic devices. In this work, we synthesize a new strong acceptor unit by converting the fluorine groups on the naphthobisthiadiazole (NTz) moiety into cyano groups via a nucleophilic aromatic substitution reaction. As a result, the p-type character observed for polymers based on NTz and difluorinated NTz is switched into an ambipolar and/or n-type character in polymers based on dicyano NTz because of the significantly improved electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…A series of copolymers (P40a−P40d) based on CN‐naphthobisthiadiazole (CNNTz) and bithiophene with different F atoms (0, 2F, and 4F) were synthesized by Osaka et.al. [ 128 ] Due to the introduction of the electron‐withdrawing CN groups in the NTz moiety, the HOMO/LUMO energy level of P40a was −5.49/−3.66 eV, which was lower than that of the analogues based on NTz and F‐NTz. [ 129,130 ] In addition, increasing the F atoms on the 2T moieties gradually lowered the HOMO and LUMO energy levels from P40a to P40d.…”
Section: Improving the Electron Transport Of D–a‐type Sps Via Amsmentioning
confidence: 99%
“…A series of copolymers (P40a−P40d) based on CN‐naphthobisthiadiazole (CNNTz) and bithiophene with different F atoms (0, 2F, and 4F) were synthesized by Osaka et.al. [ 128 ] Due to the introduction of the electron‐withdrawing CN groups in the NTz moiety, the HOMO/LUMO energy level of P40a was −5.49/−3.66 eV, which was lower than that of the analogues based on NTz and F‐NTz. [ 129,130 ] In addition, increasing the F atoms on the 2T moieties gradually lowered the HOMO and LUMO energy levels from P40a to P40d.…”
Section: Improving the Electron Transport Of D–a‐type Sps Via Amsmentioning
confidence: 99%
“…[15][16][17] Nowadays, many high-performance CPs in OSCs and OFETs contain branched alkyl chains. [18][19][20][21][22][23][24][25][26][27][28] Some studies indicate that changing the branching point of alkyl chains can vary the packing of CPs, leading to different lm morphology and device performance. 29,30 Manipulating the alkyl chain branching point has become an effective strategy to improve the performance of CPs in OSCs and OFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthobischalcogenadiazole (NXz) units, such as naphtho­[1,2- c :5,6- c ′]­bis­[1,2,5]­thiadiazole (NTz), naphtho­[1,2- c :5,6- c ′]­bis­[1,2,5]­oxadiazole (NOz), , and their derivatives, are emerging acceptor units for high-performance π-conjugated polymers (Figure a). Due to the large π-electron systems that can induce strong π–π intermolecular interaction, π-conjugated polymers based on these building units can give highly ordered packing structures and thus high charge carrier mobilities in OFETs. ,,,, Interestingly, whereas polymers based on NTz showed p-type characteristics, those based on NOz showed the ambipolar behavior due to the enhanced electron deficiency in NOz relative to that in NTz . We have recently reported a series of polymers based on dicyano NTz (CN-NTz), which also exhibits enhanced electron deficiency compared to NTz, and found that the polymers have ambipolar to n-type semiconducting characteristics depending on the co-monomer unit in the backbone .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large π-electron systems that can induce strong π–π intermolecular interaction, π-conjugated polymers based on these building units can give highly ordered packing structures and thus high charge carrier mobilities in OFETs. ,,,, Interestingly, whereas polymers based on NTz showed p-type characteristics, those based on NOz showed the ambipolar behavior due to the enhanced electron deficiency in NOz relative to that in NTz . We have recently reported a series of polymers based on dicyano NTz (CN-NTz), which also exhibits enhanced electron deficiency compared to NTz, and found that the polymers have ambipolar to n-type semiconducting characteristics depending on the co-monomer unit in the backbone . We have also focused on π-conjugated polymers based on naphtho­[1,2- b :5,6- b ′]­bispyrazine (NPz), which is an analogue of NXz (Figure a), , whereas other groups have reported NPz-based polymers as p-type semiconductors for OPVs. An important feature of NPz is that it allows the introduction of four substituents at 2-, 3-, 8-, and 9-positions, in contrast to NTz and NOz.…”
Section: Introductionmentioning
confidence: 99%